DiMarco, D. and Ruppert, T. (Eds.). (2022). Avian Aesthetics in Literature and Culture: Birds and Humans in the Popular Imagination. - Kvangraven, Endre Harvold (Journal of Ecohumanism, 2023)
DiMarco, D. and Ruppert, T. (Eds.). (2022). Avian Aesthetics in Literature and Culture: Birds and Humans in the Popular Imagination. Lexington Books. 262 pages. ISBN: 9781666901825 (e-book) ISBN: 9781666901818 (hardback)